Mapping ecotheologies: Deliberations on difference - Eaton, Heather (Theology, 2013)
How do we understand differences in our approaches, methods and priorities? This reflection explores three areas of differences in the field of ecotheology: topics, methods and the specific concerns and presuppositions of the people involved.